Hebrews 3:6b and 3:14 Revisited - Wilson, Andrew J. (Tyndale bulletin, 2011)
Hebrews 3:6b and 3:14 have been central to Reformed interpretations of the warnings in Hebrews for several centuries. Today, however, there is something of an impasse in scholarship: on one side, there are those who see these verses as an interpretive key to the letter, and thus understand the warnings to refer to spurious or false believers; on the other, there are those who argue that since Hebrews warns real believers away from real apostasy, these two verses cannot mean what, at a grammatical level, they appear to mean. In this paper, I appraise the scholarly discussion so far, identify three key issues relating to grammar and context, and then propose a way through the impasse that has not been considered in modern scholarship.